A framework for short- vs. long-term risk indicators for outsourcing potential for enterprises participating in global value chains: Evidence from Western Balkan countries - Jolta Kacani; Lindita Mukli; Eglantina Hysa (Journal of Risk and Financial Management, 2022)
This paper aims to present a benchmarking framework for short- and long-term risk of enterprises in emerging markets that seek integration in global value chains. The benchmark instrument aims in particular to assess short- and long-term risk based on accounting data and estimations of key financial ratios for enterprises located in the Western Balkan region and operating in the materials, industrials, and customer-discretionary industries. In total, the paper considers 310 enterprises. Given the geographical proximity of the region, the benchmark instrument for short- and long-term risks serves to assess the outsourcing potential these enterprises have toward foreign enterprises dominating larger markets such as the European value chain. The framework is applicable to a large-scale annual data series collected on subindustry level in order to obtain a more granular analysis of a particular industry and its respective value chain. The benchmarking instrument indicates that those subindustries performing better both at short- and long-term risk display a higher outsourcing potential and more opportunities for integration in global value chains.
Keywords: 650; accounting data; financial ratios; financial risk; global value chains; outsourcing potential